Analisis Dampak Longsoran Gunung Bawakaraeng Terhadap Laju Sedimentasi Waduk Bili-Bili - Astuti Risky Amalia; Amrullah Mansida; Nenny Karim T (Journal of Innovation Research and Knowledge, 2026)
The landslide in the Bawakaraeng Caldera in March 2004 produced approximately 200–300 million m³ of debris, which flowed into the Jeneberang River and caused sedimentation in the Bili-Bili Reservoir. This study aims to analyse the potential for landslides, the impact of landslides on sediment transport at Sabo Dams 7-7, 7-6, and 7-5, and the rate of sedimentation entering the reservoir. The methods employed include the MUSLE (Modified Universal Soil Loss Equation) for erosion analysis, the Meyer-Peter Müller (MPM) method for bedload sediment transport, and analysis of suspended sediment discharge using AWLR data. The results indicate that the landslide potential reaches 313.349 tonnes/year (830.593 m³/year), classified as very high. The highest sediment transport occurs at Sabo Dam 7-7 at 787.171m³/year, followed by a decrease at Sabo Dam 7-6 at 753.491m³/year and Sabo Dam 7-5 at 228.439 m³/year. Sediment entering the Bili-Bili Reservoir exhibits a seasonal pattern, with total accumulation reaching 799,170,000 m³ by 2025. The conclusions of this study indicate that landslides from Mount Bawakaraeng have a significant impact on increased sedimentation, and that the presence of sabo dams is capable of retaining some sediment, although they are not yet fully optimal